OpenFOAM® simulation of the injection moulding filling stage - Magalhães, Ana Cláudia Leite (2016)
The main purpose of this work is the simulation of the injection moulding filling stage using the open source software OpenFOAM® (version 2.3.1). The program can already solve general problems, but, we would like to extend its capabilities, by creating and implementing a new boundary condition capable of letting the air out of the mould, but not the polymer. We consider different locations for the air exit and study their influence on the quality of the final results. In addition, since the material viscosity influences the evolution of the flow front and its behaviour inside the mould, we also study the filling of the mould cavity considering both a Newtonian and a generalized Newtonian model (Bird- Carreau) fluids. In order to take into account non-isothermal flows, we have implemented the energy equation in the interFoam solver. We also added a temperaturedependent viscosity model (the Cross model) modified with the Arrhenius equation. The solver interFoam was also extended to viscoelastic flows, and simple tests were performed using an Oldroyd-B model. Finally we have performed simulations of the filling process of a real injection part, a tensile specimen and its feeding system.